Integration of immigrants: a current view of four cases from Europe - Saltik, Serkan (Universitätsbibliothek Heidelberg, 2015)
This paper probes into the integration conditions the third-country nationals currently enjoy in Germany, the UK, Greece and Italy. The analysis is based on recent data provided by the Eurostat and Migration Policy Index. Based on a set of indicators concerning labour markets, education, health, family reunion, long-term residence, political participation, access to nationality and anti-discrimination, as pointed out at the 2010 EU Council, the paper notes significant divergences between the selected Member States vis-à-vis the EU norms and conditions on that score.